Design, manufacture, modelling and testing of surface acoustic wave strain sensors - Mc Cormack, Brian (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2008)
There is an increasing demand for multi-sensor strain measurement systems, particularly those which incorporate wireless sensors. A possible application of such a system is the Real-Time Weigh-In-Motion (RTWIM) of heavy goods vehicles. Surface Acoustic Wave (SAW) strain sensors have been proposed for this application as they offer both wireless interrogation and passive operation, but considerable development work is required before they can be successfully deployed. This thesis details the design, manufacture, modelling and testing of SAW strain sensors for the RTWIM application. Following a discussion of surface wave theory and devices, the design and manufacture of the prototype sensors is detailed. This is achieved through a new system which integrates the design and manufacturing processes from initial sensor specifications to finished devices, thus yielding significant improvements over existing schemes. Sensor modelling is achieved through new modifications to the coupling-of-modes (COM) SAW model, which allows both the complete frequency responses of the devices, and their sensitivity to biases, to be simulated. The prototype sensors are then tested in both unstrained and strained states, thus enabling the evaluation of both the device fabrication and the COM modelling. Although issues were encountered with each of the research strands, this work successfully extends and improves the development of SAW strain sensors. It is hoped that the research can facilitate the deployment of these innovative sensors in a range of applications.
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin